2016
DOI: 10.1161/strokeaha.115.010828
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Artery Occlusion and the Risk of Stroke Development

Abstract: Background and Purpose— Our aim was to evaluate the risk of subsequent stroke development after retinal artery occlusion (RAO). Methods— National registry data were collected from the Korean National Health Insurance Service, comprised 1 025 340 random subjects. Patients diagnosed with RAO in 2002 and 2003 were excluded. The RAO group was composed of patients with an initial diagnosis of either central or other RAO between January 2004 and December 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 33 publications
11
83
5
Order By: Relevance
“…Vasculitis also is associated with RAO, 29,33 including giant cell arteritis, which had the highest OR among all RAO risk factors in the present study. Giant cell arteritis has been implicated in ocular syndromes, including blindness, 28 and is often accompanied by other vascular diseases; thus, it may be a marker for vascular disease.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Vasculitis also is associated with RAO, 29,33 including giant cell arteritis, which had the highest OR among all RAO risk factors in the present study. Giant cell arteritis has been implicated in ocular syndromes, including blindness, 28 and is often accompanied by other vascular diseases; thus, it may be a marker for vascular disease.…”
Section: Discussionsupporting
confidence: 54%
“…12,31,32 Hospital conditions included anemia, transfusion, cardiogenic shock, and postoperative bleeding. Stroke was included as embolic, thrombotic, transient ischemia, and “other.” 33 …”
Section: Methodsmentioning
confidence: 99%
“…The NHIS then established the nationwide National Sample Cohort (NHIS-NSC)—a database that provides public health information, such as the participants’ medical bill expenses claimed by medical service providers. A total of 1,025,340 nationally representative subjects were randomly selected from the Korean population in 2002, which amounts to ~2.2% of the population, and were followed until 2013 11 . Proportionate stratified random sampling was conducted based on a total of 1476 strata.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis from the Korean National Health Insurance claims data indicated that patients with CRAO carry a 1.78 fold increased risk (95% confidence interval, 1.32 – 2.41) of development of cerebral stroke within 4 years when compared to a cohort of age-matched controls. 5 A 2016 review of retrospective cohort-control comparison studies (324,518 total cases) indicated that patients presenting with retinal artery occlusion had a higher lifetime development of cerebrovascular disease including myocardial infarction and stroke (odds ratio of 2.01; 95% confidence interval: 1.21–3.34). 6 In fact, 23–24% of patients with acute retinal ischemia have MRI evidence of concurrent silent cerebral infarctions, as seen in three retrospective studies of a combined 375 patients who were imaged with diffusion-weighted MRI at time of visual loss.…”
Section: Epidemiology Risk Factors and Prognosismentioning
confidence: 99%